Glacial evolution of Sierra Nevada (Spain) and the origin of rock glaciares - Ortiz, Antonio Gómez (2013)
In spite of considerable advances in the knowledge and understanding of the glacial chronology of southern Europe, some very significant mountains still have to be studied. These include the Sierra Nevada, the highest mountain range in the Iberian Peninsula, located in the extreme south-east, only 170 km from Africa, where the last glaciers disappeared last century. The aim of this paper is to present a chronology of deglaciation from the Sierra Nevada based on geomorphological analysis of glacial and periglacial landforms and on 36Cl surface exposure dating, then to relate it to the historical Little Ice Age (LIA) deglaciation process reconstructed from field data and historical documentary sources.